2010
DOI: 10.1080/0161956x.2010.491432
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Changing Culture in Small High Schools: Reform Models and Changing Instruction With Project-Based Learning

Abstract: This study describes the status of small school reforms in U.S. high schools and contemplates their future. It asks how cultural and instructional reforms differ across school reform types. Analyses focus on indicators of teacher and student culture as well as instructional reforms including projectbased learning (PBL) and other inquiry-related practices. Findings are based on data from a national survey completed by 395 high school teachers who were responsible for and had used PBL in core academic subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 25 publications
1
60
0
Order By: Relevance
“…The establishment of such networks was reported to be essential for effective school reform during a ten year study in one English local authority (Ainscow, 2010). This sort of systematic subscription to the school reform process is reported to be vital to promoting change within USA schools (Ravitz, 2010;Beabout, 2010). It would appear that similar systemic commitment would make for favourable conditions for school reform in Scotland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of such networks was reported to be essential for effective school reform during a ten year study in one English local authority (Ainscow, 2010). This sort of systematic subscription to the school reform process is reported to be vital to promoting change within USA schools (Ravitz, 2010;Beabout, 2010). It would appear that similar systemic commitment would make for favourable conditions for school reform in Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…A study involving the implementation of 395 high schools in the USA found that it was often difficult to change pupil instruction during school reform. One of the major issues in determining the ability of school reform to change student instruction was whether or not the school has systemically subscribed to the proposed reform model (Ravitz, 2010). To aid this process, feedback from school reform partners to schools was reported to be important in a study of ten schools undertaking reform in the aftermath of hurricane Katrina in the USA (Beabout, 2010).…”
Section: Evidence Of School Reformmentioning
confidence: 99%
“…It is often difficult to change student instruction during school reform without systematic subscription to the proposed reform (Ravitz, 2010). These factors themselves echo social interdependence theory (Johnson et al, 2010) as school reform requires: systematic structures of staff support, standardized resources and pedagogies promoting positive teacher interdependence, and teacher buy-in.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to new technologies and increased interest in PjBL, we have seen widespread high school reform initiatives, notably converting large comprehensive high schools into smaller schools to help personalize relationships and support more effective teaching and learning (Bloom, Thompson, Unterman, Herlihy, & Payne, 2010;Kahne, Sporte, de la Torre, & Easton, 2006;Ravitz, 2010). A few organizations have sought to push instructional boundaries in conjunction with more holistic school reform models (Bodilly, Purnell, Ramsey, & Keith, 1996).…”
Section: Reforming High Schoolsmentioning
confidence: 99%
“…Schools affiliated with these reform networks benefit from having a central organization to help sustain the model's philosophy and practices. In addition to online technologies, they have structures that support multidisciplinary teaching, provide a repertoire of practices, and a supportive culture for teaching and learning (Ravitz, 2010).…”
Section: Reforming High Schoolsmentioning
confidence: 99%